(untitled) (Biological Sciences - PJSIR, 2003)
Morphological studies on the Schistosoma mansoni and S. margrebowiei schistosomulum development in the lung of definitive host mouse have been reported after 2 to 21 days post-infection. The greatest proportion of schistosomula were observed within the capillaries attached to the alveoli and few in the branches of the pulmonary arteries and veins. The length and shape of schistosomulum sections were highly variable due to the randomness of the plane of sections through the worm. The differences in the diameter of the body and cuticle of the S. mansoni and S. margrebowiei schistosomulum were non-significant (P > 0.05).